Sensitivity of the Molecular Test in Saliva for Detection of COVID-19 in Pediatric Patients With Concurrent Conditions - Guzmán-Ortiz Ana Laura; Nevárez-Ramírez Abraham Josué; López-Martínez Briceida; Parra-Ortega Israel; Angeles-Floriano Tania; Martínez-Rodríguez Nancy; Jamaica-Balderas Lourdes; De la Rosa-Zamboni Daniela; Ortega-Riosvelasco Fernando; Jaramillo-Esparza Carlos Mauricio; Bonilla-Pellegrini Sergio René; Reyna-Trinidad Irineo; et al. (Frontiers Media S.A., 2021)
Background: The reference standard for the molecular diagnostic testing for COVID-19 is the use of nasopharyngeal or combined nasopharyngeal and oropharyngeal (NP/OP) swabs. Saliva has been proposed as a minimally invasive specimen whose collection reduces the risks for health care personnel.Objective: To assess the suitability of saliva for COVID-19 diagnosis as a replacement of the reference standard NP/OP swab in the setting of a tertiary care pediatric unit.Study design: A paired study based in the prospective cohort design in patients suspected of having COVID-19.Methods: RT-PCR was used to detect SARS-CoV-2 in paired samples of saliva and NP/OP swab collected from May through August 2020 from 156 pediatric participants, of whom 128 has at least one comorbidity and 91 showed clinical symptoms related to SARS-CoV-2 infection. Additionally, we studied a group of 326 members of the hospital staff, of whom 271 had symptoms related to SARS-CoV-2 infection.Results: In the group of pediatric participants the sensitivity of the diagnostic test in saliva was 82.3% (95% CI 56.6-96.2) and the specificity 95.6% (95% CI 90.8-98.4). The prevalence of COVID-19 was 10.9% (17/156). In 6 of the 23 participants who tested positive for SARS-CoV-2 in at least one specimen type, the virus was detected in saliva but not in NP/OP swab, while in 3 participants the NP/OP swab was positive and saliva negative. In the group of adults, the sensitivity of the test in saliva was 77.8% (95% CI 67.2-86.3) and prevalence 24.8% (81/326). Discordant results between the two types of specimens showed a significant association with low viral load in the pharynx of adults but not of pediatric participants.Interpretation: In the context of a pediatric tertiary care hospital, the sensibility of the test in saliva is not high enough to replace the use of NP/OP swab for COVID-19 diagnosis. Neither NP/OP swab nor saliva could detect all the participants infected with SARS-CoV-2.